Hymn (Christian Ethics) - Siering, Timm (SysLex, 2026)
Essentially, two ethical perspectives can be distinguished when it comes to the Church hymn, both of which emerge out of the formal character (Gestalt) of this genre of music. First, we are with the Church hymn dealing exclusively with text-bound music. These texts can be the object of ethical analysis with respect to their inherent claims about human existence or with respect to the ways in which they either prompt action or the omission of action. Second and even more primarily, the ethical implications of the Church hymn disclose themselves in the performative dimension. Participation in and through music in particular situational contexts has demonstrable effects on the body that are worthy of ethical consideration. The emphasis in this essay lies on the music.